U-571 [videorecording (DVD)] - Mostow, Jonathan; De Laurentiis, Dino; McConaughey, Matthew, 1969-; Paxton, Bill; Bon Jovi, Jon; Keitel, Harvey (Universal Studios, 2000)
During World War II, a group of Navy men are sent to steal Enigma (the nazis' top-secret decoding device). When their own ship is destroyed, they must secretly make their way through hostile waters in a severely damaged Nazi U-boat to safety with the device.